Evaluation of the Implementation of an Excel-Based Financial Recording System in Micro Enterprises: A Case Study of Mon Kopi Cafe - Hetining Setyowati; Wikan Budi Utami; Hadi Samanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to evaluate the implementation of a Microsoft Excel-based financial recording system in a micro business, using Mon Kopi Café as a case study. The background of this research is based on the importance of orderly and systematic financial management for micro-enterprises, where Microsoft Excel serves as a practical and cost-effective tool. This research employs a qualitative approach with a case study method. Data collection techniques include interviews, observation, and documentation. The results indicate that the use of Excel at Mon Kopi Café has been carried out actively and is fairly effective in supporting daily transaction recording and the preparation of monthly financial reports. The system also supports business decision-making by providing structured financial data. However, several challenges were identified, such as incorrect use of formulas, lack of standardized formats, and limited technical skills among staff. Nevertheless, the Excel-based financial recording system is considered effective for micro-scale businesses, particularly when supported by training and improved human resource capacity.